Status mniejszości narodowych i etnicznych i ich ochrona w Konstytucji Rzeczypospolitej Polskiej oraz w podstawowych ustawach ustrojowych Zjednoczonego Królestwa Wielkiej Brytanii i Irlandii Północnej. Analiza porównawcza wybranych aspektów = The status of national and ethnic minorities and their protection in the Polish Constitution and the fundamental constitutional laws of the United Kingdom of Great Britain and Northern Ireland. Comparative analysis of selected aspects - Kuczer, Jarosław (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
Attempts to codify the rights of national minorities and ethnic date back to its roots in the early nineteenth century. For a long time their definition referred only to the area of European legal culture. This article presents the way of understanding, on the legal level, the problem of the protection of minorities in the two European countries. The diversity of legal culture of the United Kingdom, discrepancies with continental, even as advanced as in the Polish Republics, remain very large.
Keywords: Konstytucja RP z dnia 2 kwietnia 1997 r.; Equality Act; mniejszości narodowe; mniejszości etniczne; prawa mniejszości; Powszechna Deklaracja Praw Człowieka; prawa człowieka; Europejska Karta Języków Mniejszościowych i Regionalnych; Ustawa o Mniejszościach Narodowych i Etnicznych; Constitution of Republic of Poland; National and ethnic minorities; minority rights; Universal Declaration of Human Rights; human rights; European Charter for Regional or Minority Languages; Bill on Ethnic and National Minorities and Regional Languages